The Grand (Ducal) Finale: Anna Maria Luisa as the last Medici Patron of the San Lorenzo Basilica in Florence - Cantell, Sointu (Incontri. Rivista europea di studi italiani, 2024)
The San Lorenzo Basilica in Florence is renowned for its Medici-infused Renaissance program, but there is a lesser-known phase of the Medici family’s history in the basilica that unfolded in the 18th century. Between 1738 and 1743, Anna Maria Luisa de’ Medici, the last surviving member of the Medici line, oversaw extensive architectural and decorative interventions within the San Lorenzo complex. Her efforts to maintain the cultural heritage of her ancestors were heavily shaped by the imminent end of the Medici bloodline and the difficult transition of the Grand Duchy of Tuscany to the House of Habsburg-Lorraine. This article explores Anna Maria’s motivations for her elaborate renovation projects in the basilica, with a particular focus on two of her most notable commissions: Vincenzo Meucci’s cupola fresco in the nave of the basilica and the new bell tower designed by architect Ferdinando Ruggieri. These two projects, the only ones completed by Anna Maria before her death, demonstrate her ambitions within the San Lorenzo and help to uncover several underlying premises for their conceptions.